1972
DOI: 10.1037/h0033638
|View full text |Cite
|
Sign up to set email alerts
|

Prediction outcome and choice reaction time: A memory-dependent relationship.

Abstract: In two-choice reaction time (RT) situations, the interval between the prediction and the presentation of successive stimuli was either 3, 7, or 11 sec. The 20 5s of one group (Group Stim) pressed a left-hand trigger following one stimulus and a right-hand trigger following the alternative stimulus; 5s of another group (Group Pred) identified the prediction outcome on each of the 200 trials by making one response if the prediction was correct and the other response following an incorrect prediction. The influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

1974
1974
1982
1982

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…The assumption implicit in either proeedure is that, onee a verbal prediction has been uttered, it will remain in memory, unchanged, until the stimulus in presented. Geller and Whitman (1972) have ehallenged this assumption by varying the time between a subject's predietion and the stimulus from 3 to 11 sec. Their results showed that, as the PSI inereased, the differenee in RT between eorreetly and ineorreetly predicted stimuli decreased, that is, aPrediction Outeome by PSI interaction.…”
mentioning
confidence: 99%
“…The assumption implicit in either proeedure is that, onee a verbal prediction has been uttered, it will remain in memory, unchanged, until the stimulus in presented. Geller and Whitman (1972) have ehallenged this assumption by varying the time between a subject's predietion and the stimulus from 3 to 11 sec. Their results showed that, as the PSI inereased, the differenee in RT between eorreetly and ineorreetly predicted stimuli decreased, that is, aPrediction Outeome by PSI interaction.…”
mentioning
confidence: 99%
“…The apparatus and general procedure were similar to those used by Geller and Whitman (1972). The order of events on each of 198 RT trials were as follows: (1) The experimenter prompted the subject's stimulus prediction by illuminating the center, horizontal line (1.3 cm) of the seven-segment stimulus readout; (2) the subject predicted which of the two possible stimulus events would occur, a U symbol (called up) or a n symbol (called down); (3) with the left forefinger, the subject depressed one of two spring-return levers to indicate a stimulus prediction (these prediction levers were located on a panel to the left of the subject and were separated on a vertical axis by 7.7 cm; the uppermost lever was used to designate a prediction of U); (4) the subject's depression of the prediction lever initiated a time interval of 3, 7, or 11 sec; (5) a .25 -sec "ready" buzzer occurred and initiated a fixed interval of 1.5 sec; (6) the U or n symbol (5 x 1.3 cm) was presented by illuminating the appropriate segments of the seven-segment stimulus readout; (7) the subj·ect identified the stimulus presentation as quickly as possible by pulling a left-or right-hand reaction trigger.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Supporting this simple expectancy interpretation of the PO effect are the observed relationships between choice RT and factors that presumably qualify the subject's stimulus predictions. For example, choice RT to correctly predicted stimuli was an inverse function of the confidence associated with the prediction , the probability of a correct prediction (Geller, 1974;, and the relative frequency of the stimulus predicted (e.g., Geller & Pitz, 1970; Geller, Whitman, Wrenn,& Shipley, 1971).The present research was designed to follow up an observation that the PO effect decreased as the interval between th~ subject's prediction and the stimulus presentation mcreased (Geller & Whitman, 1972). In the Geller and Whitman study, the prediction-to-stimulus (P-S) interval was 3, 7, or 11 sec, varying randomly among the 198 trials for each subject.…”
mentioning
confidence: 99%
See 2 more Smart Citations